2017
DOI: 10.1177/1528083717702008
|View full text |Cite
|
Sign up to set email alerts
|

Development of biomass-derived functionalized activated carbon-coated and polyaniline-grafted cotton fabric with enhanced ultraviolet resistance

Abstract: Cotton fabric with enhanced ultraviolet shielding behavior was successfully developed by coating functionalized activated carbon and grafting polyaniline hybrid material through in situ polymerization. Initially, the activated carbon was prepared from bio-mass rice husk and then surface functionalized using suitable silane coupling agent. The optimized sample delivers strong ultraviolet shielding ability with a Ultraviolet Protection Factor (UPF) value of 63.9, which is nearly 20 times higher than that of pris… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 62 publications
0
6
0
Order By: Relevance
“…Nonwoven cotton fabrics were washed with distilled water and soaked in 2 M NaOH solution and heated to 100 °C for 3 h for surface activation and removal of any greasy material. 34 After that, the fabric was taken out and washed again with distilled water and kept drying at 60 °C for 10 h. After drying, the pristine cotton fabrics were cut to appropriate sizes and weighed. Exactly 1 g of the BF and PYBP monomers was weighed separately in a beaker, and 10 mL of THF was added and stirred for 10 min to completely dissolve the monomers.…”
Section: Methodsmentioning
confidence: 99%
“…Nonwoven cotton fabrics were washed with distilled water and soaked in 2 M NaOH solution and heated to 100 °C for 3 h for surface activation and removal of any greasy material. 34 After that, the fabric was taken out and washed again with distilled water and kept drying at 60 °C for 10 h. After drying, the pristine cotton fabrics were cut to appropriate sizes and weighed. Exactly 1 g of the BF and PYBP monomers was weighed separately in a beaker, and 10 mL of THF was added and stirred for 10 min to completely dissolve the monomers.…”
Section: Methodsmentioning
confidence: 99%
“…In addition, the quinonoid and benzenoid rings of PANI also possessthe strong UV absorption behavior due to their C=C skeleton and thereby provides the e cient UV shielding effect. It is reported that the energy of C=C bonds is about 335 kJ which is approximately equal to the energy of UV photons [58]. Thus, synergistic effect of both poly(C-ddm) and polyaniline contributes to the UV shielding behavior, which are in equivalent to those of high cost graphene, metal oxide coated cotton fabric [59][60][61].…”
Section: Morphology Of Poly(c-ddm) and Pani/ Poly(c-ddm)mentioning
confidence: 96%
“…Spectral and morphology of treated cotton fabrics: cm -1 respectively. Since the fabric was treated with sodium hydroxide, the primary hydroxyl groups might have been oxidized to the carboxylic group [58]. After coating with PANI, due to the presence of only 2 wt % coating, the respective bands corresponding to quininoid and benzenoid rings of polyaniline usually occurred at 1571 and 1476 cm −1 shows very weak signals.…”
Section: Morphology Of Poly(c-ddm) and Pani/ Poly(c-ddm)mentioning
confidence: 99%
“…Variety of substrates like sponges (Peng et al 2019), porous ceramics (Dong et al 2019a), metallic meshes (Kang et al 2017) and textiles (Sharma et al 2020) with superhydrophobicity have been investigated towards oil-water separation after suitable surface modification. In particular, cotton is believed to be a promising substrate in virtue of its ubiquitous, low cost, flexible, biodegradable and excellent mechanical strength (Thennarasu et al 2018;Zhou et al 2019;Chauhan et al 2019;Ahmad et al 2019;Zhao et al 2020). However, cotton fabric has great absorbency with both oil as well as water instantaneously due to the presence of surface polar groups.…”
Section: Introductionmentioning
confidence: 99%